(untitled) (Sociologisk Forskning, 2001)
“If she is alive, people want to see more and more”: Gossip, divided femaleness and honour among Swedish women from the Middle East This article analyses how Swedish women from the Middle East talk about gossip. In interviews, the women talk about a “good reputation” as something “necessary” and “very important”, and about “bad reputation” as something one has to avoid at any cost. Using a contextual and relational understanding ofthe concepts of “identity” and “culture”, the article analyses the women’s talk about gossip as a construction of gender identity in the eyes of “others”. This construction, it is argued, is related to a contrast between what others can see and what others cannot see. Further, it can be analysed in the light of cultural notions of divided femaleness, here understood as a construction of “the whore” - an irrevocably stained woman - and “the virgin” - a pure and untouched woman - as mutually exclusive categories. Through this analysis, a widened understanding of the concept of honour is reached, where different cultural notions, like gossip, hijab, honour and divided femaleness are held together.